A Comparison Between Virtual and Conventional Microscopes in Health Science Education - Sharmin, Nazlee; Chow, Ava K.; Dong, Alice S. (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2023)
Virtual microscopes are computer or web-based programs that enable users to visualize digital slides and mimic the experience of using a real light microscope. Traditional light microscopes have always been an essential teaching tool in health science education to observe and learn cell and tissue structures. However, studies comparing virtual and real light microscopes in education reported learners’ satisfaction with virtual microscopes regarding their usability, image quality, efficiency, and availability. Although the use of virtual or web-based microscopy is increasing, there is no equivalent decrease in the number of schools utilizing traditional microscopes. We conducted a scoping review to investigate the comparative impact of conventional and virtual microscopes on different aspects of learning. We report a relative effect of virtual and light microscopy on student performance, long-term knowledge retention, and satisfaction. Our results show that virtual microscopy is superior to traditional microscopes as a teaching tool in health science education. Further studies are needed on different learning components to guide the best use of virtual microscopy as a sole teaching tool for health care education.